2021
DOI: 10.1021/jacs.1c10151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Isolation of a Kinetically Stabilized Crystalline Triangulene

Abstract: The synthesis and isolation of hydrocarbons with a triplet ground state in crystalline forms have been sought in materials science. Triangulene is one of the most famous tripletground-state benzenoid hydrocarbons. Its unique electronic structure and highly symmetric structure have prompted many scientists to synthesize and isolate triangulene and its derivatives, but all attempts so far to isolate them as crystals have been unsuccessful. Herein we report the synthesis and isolation of a kinetically stabilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
85
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 52 publications
(58 reference statements)
1
85
0
1
Order By: Relevance
“…Simultaneously to this work, 27 Shintani et al 28 reported the synthesis of a persistent triangulene derivative kinetically stabilized by six substituents (Fig. 1, middle), which allowed its isolation in the solid state and structure confirmation by X-ray crystallography.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…Simultaneously to this work, 27 Shintani et al 28 reported the synthesis of a persistent triangulene derivative kinetically stabilized by six substituents (Fig. 1, middle), which allowed its isolation in the solid state and structure confirmation by X-ray crystallography.…”
mentioning
confidence: 62%
“…The precise addition of oxidizing agent allows the oxidation to be performed in a stepwise fashion; first a mixture of monoradicals 8a + 8b is formed, then diradical Mes 3 -Tr . This differs from the procedure reported by Shintani et al , 28 where the last step must be performed under reductive conditions. The oxidation method allows formation of pristine triangulene monoradical and its analysis by X-ray diffraction (Fig.…”
mentioning
confidence: 66%
See 3 more Smart Citations